2019
DOI: 10.1108/jsbed-08-2018-0252
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating policy approaches for tackling informal entrepreneurship

Abstract: Purpose When tackling the informal economy, an emergent literature has called for the conventional rational economic actor approach (which uses deterrents to ensure that the costs of undeclared work outweigh the benefits) to be replaced or complemented by a social actor approach which focusses upon improving tax morale. The purpose of this paper is to explore the effectiveness of these two policy approaches in reducing informal sector entrepreneurship. Design/methodology/approach To evaluate this, data are r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 59 publications
0
8
0
1
Order By: Relevance
“…Redistributive justice refers to whether they believe that they receive the goods and services they feel that they deserve given the taxes they pay (Richardson and Sawyer, 2001) and procedural justice to the extent to which they feel that the tax authority has treated them in a respectful, impartial and responsible manner (Braithwaite and Reinhart, 2000;Murphy, 2005). Secondly, formal institutions need to provide greater social protection, less public sector corruption and more effective social transfer mechanisms, all of which have been revealed to be strongly associated with lower levels of informal entrepreneurship (Autio and Fu, 2015;Dau and Cuervo-Cazzurra, 2014;Horodnic and Williams, 2019;Klapper et al, 2007;Thai and Turkina, 2014;Williams, 2017Williams, , 2019.…”
Section: Discussionmentioning
confidence: 99%
“…Redistributive justice refers to whether they believe that they receive the goods and services they feel that they deserve given the taxes they pay (Richardson and Sawyer, 2001) and procedural justice to the extent to which they feel that the tax authority has treated them in a respectful, impartial and responsible manner (Braithwaite and Reinhart, 2000;Murphy, 2005). Secondly, formal institutions need to provide greater social protection, less public sector corruption and more effective social transfer mechanisms, all of which have been revealed to be strongly associated with lower levels of informal entrepreneurship (Autio and Fu, 2015;Dau and Cuervo-Cazzurra, 2014;Horodnic and Williams, 2019;Klapper et al, 2007;Thai and Turkina, 2014;Williams, 2017Williams, , 2019.…”
Section: Discussionmentioning
confidence: 99%
“…Until now, most governments have focused on increasing the costs of informality by increasing the penalties for operating informally and improving the risk of detection (Allingham and Sandmo, 1972;Williams, 2014). Perhaps greater emphasis now is required on improving the benefits of formality (Horodnic and Williams, 2019;Scott and Haskei, 2015). This could include providing formal enterprises with access to credit, training, marketing support (e.g., trade fairs), business advice and support, belonging to business associations, and new market opportunities such as contracts with large firms and public sector procurement contracts (Fajnzylber et al, 2009;Skousen and Mahoney, 2015;.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, this has further developed. It has been suggested that institutional incongruence in the form of trust in institutions, operates at a micro-level (personal norms), meso-level (trust in others similar and close to oneself, namely horizontal trust) and macro-level (trust in state institutions, namely vertical trust) (Horodnic and Williams, 2019). Until now, most studies on institutional incongruence have only focused upon vertical trust.…”
Section: Determinants Of Enterprise and Entrepreneurship In The Informal Sectormentioning
confidence: 99%